Association between fixed orthodontic treatment and dental caries: a 1-year longitudinal study - Alice Souza Pinto; Luana Severo Alves; Marisa Maltz; Júlio Eduardo do Amaral Zenkner (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract: This longitudinal study aimed to assess the association between the use of fixed orthodontic appliances and the incidence/increment of active caries lesions in adolescents and young adults over a one-year period. A total of 135 10-30-year-old individuals were divided into two groups: Group G0 was composed of individuals who required orthodontic treatment, but who did not undergo fixed orthodontic therapy over the study period (n=70); Group G1 was composed of individuals who used a fixed orthodontic appliance for 1 year (n=65). Data collection included a questionnaire and clinical oral examinations (plaque index, gingival index, and dental caries index), performed at baseline and after 1 year. Caries examination was performed by a single calibrated examiner, after tooth cleaning and drying, and included the recording of non-cavitated and cavitated, inactive and active lesions of all tooth surfaces. Poisson regression models were used to assess the association between the group and the following study outcomes: incidence (binary variable) and increment (counting variable). The incidence of active caries lesions was 4.8% in G0 and 39.6% in G1. The mean increment of active caries lesions was 0.14 in G0 and 0.61 in G1. G1 showed a greater risk of developing active caries lesions than G0 (incidence analysis, adjusted IRR=9.48, 95%CI=2.62-34.30; increment analysis, adjusted IRR=4.13; 95%CI=1.94-8.79). In conclusion, this study showed that individuals undergoing fixed orthodontic therapy for 1 year had a significantly higher incidence and increment of active caries lesions than those without a fixed appliance.